2002
DOI: 10.1007/s00415-002-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Localized 1 H magnetic resonance spectroscopy in mainly cortical gray matter of patients with multiple sclerosis

Abstract: The brain water fraction (R), the brain water transverse relaxation time (T2), the atrophy index (alpha) and the absolute concentration of the principal brain metabolites (NAA, Cho and Cr) were measured by localized proton magnetic resonance spectroscopy in the occipito-parietal cortex (mainly gray matter) of 15 relapsing-remitting (R-R) multiple sclerosis (MS) patients, 15 secondary progressive (SP) MS patients and 8 healthy subjects. Significantly lower values of N-acetylaspartate (NAA), creatine (Cr) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 44 publications
2
46
4
Order By: Relevance
“…It is note worthy that the two groups of CIS patients (with or without T 1 Gd-enhancing lesions) did not differ in terms of time elapsed since the first clinical onset and T 2 lesion load. Few MRS studies have reported reduction in NAA inside GM in early RRMS patients [13,18], while other studies reported no differences [19][20][21]. The same contradictory results were shown in patients at the very early stage of MS, with no NAA changes in the WM observed in two studies [37,38] and a widespread NAA decrease observed in another study using non-localized MRS technique [39].…”
Section: Discussion J Technical Aspectsmentioning
confidence: 41%
See 1 more Smart Citation
“…It is note worthy that the two groups of CIS patients (with or without T 1 Gd-enhancing lesions) did not differ in terms of time elapsed since the first clinical onset and T 2 lesion load. Few MRS studies have reported reduction in NAA inside GM in early RRMS patients [13,18], while other studies reported no differences [19][20][21]. The same contradictory results were shown in patients at the very early stage of MS, with no NAA changes in the WM observed in two studies [37,38] and a widespread NAA decrease observed in another study using non-localized MRS technique [39].…”
Section: Discussion J Technical Aspectsmentioning
confidence: 41%
“…Better knowledge of the characteristics of GM changes at the early stage of MS may offer useful new perspectives on the pathogenesis of GM injury in MS, and in this regard -MR spectroscopic imaging (MRSI) may be of value. Few MRS studies have been performed in early RRMS patients [13,[18][19][20][21] and have provided inconsistent results that may be related to the existence of neuronal dysfunction related to acute inflammation without any significant irreversible neuronal loss.…”
Section: Introductionmentioning
confidence: 99%
“…In people with multiple sclerosis (MS), changes in metabolite concentrations have been observed using 1 H-MRS in lesions, normal appearing white matter (NAWM) and cortical grey matter (CGM). A metabolite of particular interest has been N-acetyl-aspartate (NAA), which is found almost exclusively within neurons and neuronal processes in the mature brain in vivo [5], and which has been found to be reduced in lesions [1,13,28], NAWM [8,16,22,35], and CGM [8,25,36] in subjects with MS. It has been suggested that such decreases may reflect both irreversible axonal loss [4] and reversible structural or metabolic injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the initial disease presentation (RRMS), there seems no (or slight) reduction in NAA levels, however, a prominent reduction in NAA levels can be captured during progressive MS [47,49]. In accordance with progressive MS, changes in NAA levels within cortical grey matter were correlated with EDSS, auditive selective attention and cognitive performance [48,50,51].…”
Section: Current Imaging Techniquesmentioning
confidence: 72%
“…However, these imaging techniques have also been used to study cortical adaptive functions in patients with RRMS, SPMS and PPMS [47,48]. In the initial disease presentation (RRMS), there seems no (or slight) reduction in NAA levels, however, a prominent reduction in NAA levels can be captured during progressive MS [47,49].…”
Section: Current Imaging Techniquesmentioning
confidence: 99%